Rapid synthesis and turnover of brain microsomal ether phospholipids in the adult rat - Thad A. Rosenberger; Jun Oki; A. David Purdon; Stanley I. Rapoport; Eric J. Murphy (Journal of Lipid Research, 2002)
The rates of synthesis, turnover, and half-lives were determined for brain microsomal ether phospholipids in the awake adult unanesthetized rat. A multicompartmental kinetic model of phospholipid metabolism, based on known pathways of synthesis, was applied to data generated by a 5 min intravenous infusion of [1,1-3H]hexadecanol. At 2 h post-infusion, 29%, 33%, and 31% of the total labeled brain phospholipid was found in the 1-O-alkyl-2-acyl-sn-glycero-3-phosphate, ethanolamine, and choline ether phospholipid fractions, respectively. Autoradiography and membrane fractionation showed that 3% of the net incorporated radiotracer was in myelin at 2 h, compared to 97% in gray matter microsomal and synaptosomal fractions. Based on evidence that ether phospholipid synthesis occurs in the microsomal membrane fraction, we calculated the synthesis rates of plasmanylcholine, plasmanylethanolamine, plasmenylethanolamine, and plasmenylcholine equal to 1.2, 9.3, 27.6, and 21.5 nmol·g−1·min−1, respectively. Therefore, 8% of the total brain ether phospholipids have half-lives of about 36.5, 26.7, 23.1, and 15.1 min, respectively. Furthermore, we clearly demonstrate that there are at least two pools of ether phospholipids in the adult rat brain. One is the static myelin pool with a slow rate of tracer incorporation and the other is a dynamic pool found in gray matter. The short half-lives of microsomal ether phospholipids and the rapid transfer to synaptosomes are consistent with evidence of the marked involvement of these lipids in brain signal transduction and synaptic function. —Rosenberger, T. A., J. Oki, A. D. Purdon, S. I. Rapoport, and E. J. Murphy. Rapid synthesis and turnover of brain microsomal ether phospholipids in the adult rat. J. Lipid Res. 2002. 43: 59–68.